2003
DOI: 10.1021/la026546b
|View full text |Cite
|
Sign up to set email alerts
|

Ionization and pH Stability of Multilayers Formed by Self-Assembly of Weak Polyelectrolytes

Abstract: The formation of polyelectrolyte multilayers using the layer-by-layer sequential self-assembly of a weak polybase and polyacid onto a surface of Si crystal and their stability under acidic conditions were studied. The system was 12%, 20%, 25%, 37%, 90%, or 98% quaternized poly-4-vinylpyridine (Q12, Q20, Q25, Q37, Q90, or Q98) as polybases (generally abbreviated as QPVP) and poly(methacrylic acid) (PMAA) as a polyacid in buffered D2O. The adsorption and ionization of pyridine rings and carboxylic groups were qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
191
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(204 citation statements)
references
References 59 publications
13
191
0
Order By: Relevance
“…The good stability of the films at lower pH was explained by the onset of hydrogen bonding involving protonated carboxylic acid groups within the films. Moreover, the increased local ionization of weak polycarboxylic acid in the presence of a highly charged polycation in their layer-by-layer films, compared to its ionization in solution, was reported [20,21]. This induced electrostatic interaction might also play an important role in the assembly of multilayer films involving weak polyelectrolytes at relatively low pH.…”
Section: Introductionmentioning
confidence: 97%
“…The good stability of the films at lower pH was explained by the onset of hydrogen bonding involving protonated carboxylic acid groups within the films. Moreover, the increased local ionization of weak polycarboxylic acid in the presence of a highly charged polycation in their layer-by-layer films, compared to its ionization in solution, was reported [20,21]. This induced electrostatic interaction might also play an important role in the assembly of multilayer films involving weak polyelectrolytes at relatively low pH.…”
Section: Introductionmentioning
confidence: 97%
“…[9][10][11] The driving force for the stable layer association is entropic in nature and results from the release of counter-ions and water. 12,13 Issues concerning the dependence of thickness evolution, [14][15][16][17] morphology 18 and ionization (in the case of weak polyelectrolytes) 19 as a function of alternated deposition are important because they control film stability and, consequently, its final applications.…”
Section: Introductionmentioning
confidence: 99%
“…Our strategy for film construction was first based on previous studies on assembly of weak polyelectrolytes, which showed that the film thickness, molecular organization and the amount of polymer adsorbed can be controlled by simple adjustments of the pH of the dipping solution [14]. Second, we also relied on prior studies on PEM assemblies of polyelectrolytes with different permanent charge densities, which reported thicker films for polymers with lower degrees of permanent charge [15]. Figure 4 (top panel) shows dry thicknesses of (BPEI/PAA) 50 films as a function of deposition pH.…”
Section: + Ionsmentioning
confidence: 99%